The relationship between anthropometric factors and hyperuricemia in adolescent athletes. Issue 4 (July 2021) - Kuo, Kuan-Liang; Chen, Hung-Ming; Hsiao, Sheng-Huang; Chu, Dachen; Huang, Sheng-Jean; Huang, Kuo-Chin; Huang, Chiao-Yu
Abstract: Purpose: Hyperuricemia has been increasingly prevalent and linked to future cardio-metabolic risks in adolescent population. The study aims to explore the relationship between anthropometric indices and hyperuricemia among adolescent athletes. Methods: This was a cross-sectional study of 387 student athletes (218 males and 169 females; mean age, 17.4 ± 1.3 years) in Northern Taiwan in 2013–2015. We exhibited the prevalence of hyperuricemia among this population, and tested the association of serum uric acid levels with different anthropometric parameters in males and females respectively. Results: A total of 59 (27.1%) male and 37 (21.8%) female adolescent athletes had hyperuricemia. Both in male and female adolescents, several obesity-related anthropometric parameters were significantly higher in hyperuricemia groups than in non-hyperuricemia groups. The odds of having hyperuricemia significantly increased with increasing BMI, BMI z-score, waist circumference and waist-to-height ratio in logistic regression analysis. There was a U-shaped association between uric acid level and body fat percentage (BF%) in both genders. Subjects whose BF% in lowest-body-fat-percentage quintile (quintile 1) and highest-body-fat-percentage quintile (quintile 5) had higher mean serum uric acid level than subjects whose BF% in the middle three quintiles. In both genders, the odds ratio (OR) of having hyperuricemia in subjects whose BF% in quintile 1 remained significantly higher than the OR in the middle three quintiles (the reference) after adjusting for age and BMI z-score. Conclusions: In addition to the positive association between obesity and hyperuricemia, there is a U shape association between BF% and prevalence of hyperuricemia among adolescent athletes of both genders.